2012
DOI: 10.1101/lm.026369.112
|View full text |Cite
|
Sign up to set email alerts
|

The visual orientation memory of Drosophila requires Foraging (PKG) upstream of Ignorant (RSK2) in ring neurons of the central complex

Abstract: Orientation and navigation in a complex environment requires path planning and recall to exert goal-driven behavior. Walking Drosophila flies possess a visual orientation memory for attractive targets which is localized in the central complex of the adult brain. Here we show that this type of working memory requires the cGMP-dependent protein kinase encoded by the foraging gene in just one type of ellipsoid-body ring neurons. Moreover, genetic and epistatic interaction studies provide evidence that Foraging fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 35 publications
2
63
0
Order By: Relevance
“…So, which central structures of the insect brain might be involved in spatial memory and whether different processes of navigation might be controlled by different central brain structures is still unclear. While complex (but not simple) visual tasks require a functional mushroom body in Drosophila (Liu, Wolf, Ernst, & Heisenberg, 1999;Ren, Li, Wu, Ren, & Guo, 2012;Tang & Guo, 2001), the ellipsoid body, as part of the central complex, is thought to be concerned with high-order motor control (Kuntz, Poeck, Sokolowski, & Strauss, 2012;Strauss, Hanesch, Kinkelin, Wolf, & Heisenberg, 1992). Thus it is possible that high-order sensory and motor performances are processed in the mushroom body and the ellipsoid body, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…So, which central structures of the insect brain might be involved in spatial memory and whether different processes of navigation might be controlled by different central brain structures is still unclear. While complex (but not simple) visual tasks require a functional mushroom body in Drosophila (Liu, Wolf, Ernst, & Heisenberg, 1999;Ren, Li, Wu, Ren, & Guo, 2012;Tang & Guo, 2001), the ellipsoid body, as part of the central complex, is thought to be concerned with high-order motor control (Kuntz, Poeck, Sokolowski, & Strauss, 2012;Strauss, Hanesch, Kinkelin, Wolf, & Heisenberg, 1992). Thus it is possible that high-order sensory and motor performances are processed in the mushroom body and the ellipsoid body, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The latter can further be subdivided into R4 medial and R4 distal according to their position in the EB [27]. Our previous rescue experiments with the ign 58/1 and for s mutants, which have the same behavioral phenotype as ebo, revealed that IGN and FOR are required in ring neurons R3/R4d and R3, respectively [13,14]. However, induction of UAS-ebo in ebo 678 flies with the c232 driver line (expressed in R3/R4d [27,28]) did not result in a rescue of the memory loss compared to ebo 678 alone or a negative control using the Or83b driver (which is expressed exclusively in odor receptor neurons [29,30]; Figure 2A).…”
Section: Ebo Function Is Redundant In Ring Neuronsmentioning
confidence: 98%
“…This type of working memory lasts about 4 s and must be updated during every turn the fly takes [13]. Analysis of two Drosophila memory mutants in ignorant (ign) and foraging (for), which encode the ribosomal-S6 kinase II (RSKII) and cGMP-dependent protein kinase (PKG), respectively, revealed that both kinases share one signaling pathway that is required in a specific type of EB ring neurons to display an orientation memory [14].…”
Section: Introductionmentioning
confidence: 99%
“…Rover flies have a higher PKG activity level [20] and experience a much more variable environment than sitter flies due to their explorative behavioral lifestyle. The for gene has been implicated in memory formation in several studies, for instance in visual orientation memory in flies [21], and there is accumulating evidence that this gene plays an important role in natural variation in prepared learning. The more explorative rover type flies are prepared to learn fast but remember the learned information for a shorter period than sitter flies, which can, due to their less explorative behavior benefit more from long lasting memories.…”
Section: Effects Of Environmental Variation and Spatial Foraging Behamentioning
confidence: 99%
“…This is particularly interesting because the activity of this gene clearly correlates with many examples of natural variation described above. This gene acts within the nitric oxide (NO) -cGMP -PKG signaling pathway, which is known for its role in LTM formation [21,55]. A phosphodiesterase involved in regulation of intracellular cGMP levels was downregulated in LTM forms, both after a single and after 3 spaced oviposition experiences in Cotesia.…”
Section: Mechanisms Underlying Natural Variation In Learning and Memorymentioning
confidence: 99%